2006
DOI: 10.1038/sj.onc.1209429
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Bax activity is crucial for the antiapoptotic function of the human papillomavirus E6 oncoprotein

Abstract: Oncogenic types of human papillomaviruses (HPVs) cause cervical cancer in humans. The antiapoptotic viral E6 gene has been identified as a key factor for maintaining the viability of HPV-positive cancer cells. Although E6 has the potential to modulate many apoptosis regulators, the crucial apoptotic pathway blocked by endogenous E6 in cervical cancer cells remained unknown. Using RNA interference (RNAi), here, we show that targeted inhibition of E6 expression in cervical cancer cells leads to the transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 38 publications
0
46
1
3
Order By: Relevance
“…Although we have not tested this, it is most likely that E6 is responsible for this effect, possibly by promoting degradation of Bax, analogous to what has been described for Bak and HPV5 E6 . Downregulation of Bax by HPV16 and HPV18 E6 in PHK and HeLa cells, respectively, has been reported by others (Magal et al, 2005;Vogt et al, 2006), but was not observed in the early-passage HPV16 E6E7-expressing PHKs we used. In contrast, as discussed earlier, we could already observe active Bax in the unirradiated HPV16 E6E7-containing cells, which may explain the ready increase in caspase activity in HPV16-transduced cells immediately after UVB exposure (Fig.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Although we have not tested this, it is most likely that E6 is responsible for this effect, possibly by promoting degradation of Bax, analogous to what has been described for Bak and HPV5 E6 . Downregulation of Bax by HPV16 and HPV18 E6 in PHK and HeLa cells, respectively, has been reported by others (Magal et al, 2005;Vogt et al, 2006), but was not observed in the early-passage HPV16 E6E7-expressing PHKs we used. In contrast, as discussed earlier, we could already observe active Bax in the unirradiated HPV16 E6E7-containing cells, which may explain the ready increase in caspase activity in HPV16-transduced cells immediately after UVB exposure (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…Previously, most studies have shown that HPV16 E6 deregulates pro-apoptotic proteins, resulting in a reduction in the rate of apoptosis (Alfandari et al, 1999;Filippova et al, 2002Filippova et al, , 2004Magal et al, 2005;Thomas & Banks, 1998Vogt et al, 2006). None of these studies, however, used UV irradiation as a trigger of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged p53 stabilization was achieved by cisplatin in E6-suppressed HeLa cells (Koivusalo et al, 2005;Putral et al, 2005). Moreover, prolonged p53 activation resulted in the activation of the intrinsic pathway in E6-supressed HeLa cells (Vogt et al, 2006), which may occur in E6-suppressed SiHa cells as well. The decreased p21 levels after cisplatin treatment of E6-suppressed SiHa cells may affect apoptosis, because p21 not only mediates p53-induced cell cycle arrest but also can suppress apoptosis after exposure to DNA-damaging agents, such as cisplatin, and death receptor-mediated apoptosis (Koster et al, 2010).…”
Section: Hpv16 E6 Rnai Enhances Cisplatin and Dr-mediated Apoptosis 705mentioning
confidence: 99%
“…siRNAs either were expressed from vector pSuper or were chemically synthesized (Dharmacon Research). siRNAs were generated against the following target sequences, as previously described (5,18): si16E6/E7, 5 ¶-CCGGACAGAGCCCAUUACA-3 ¶ (HPV16 nucleotides 700-718); si18E6/E7, 5 ¶-CCACAACGUCACACAAUGU-3 ¶ (HPV18 nucleotides 755-773); si16E6, 5 ¶-ACCGUUGUGUGAUUUGUUA-3 ¶ (HPV16 nucleotides 385-403); and si18E6, 5 ¶-CUAACACUGGGUUAUACAA-3 ¶ (HPV18 nucleotides 385-403). EZH2 targeting siRNA siEZH2-1 (13) and vector pSuper-p53 (19) have been characterized in detail before.…”
Section: Methodsmentioning
confidence: 99%